(untitled) (Agro Productividad, 2021)
Objective: The objective was to infer the effect of the variables phenology (migration-non-migration), seasonal (rainfall-dry season), sex and forest condition on the abundances of birds (resident-migratory) in a semi-preserved and disturbed oak pine forest. Design/methodology/approach: It was carried out in Monte Tlaloc, State of Mexico, under two conditions of apparent disturbance, semi-preserved oak pine forest and disturbed oak pine forest. Ten bird samplings were carried out with "count on point" with a fixed radius of 25 m, covering the 4 seasons of the year and migratory periods. With the previous data, the Relative Abundance Index (RAI) was estimated. To infer the effect of the variables phenology, seasonality, sex and forest condition on the abundances of birds, generalized linear models were elaborated. Results: The IAR of the birds registered in the semi-considered pine forest indicates that the species with the lowest presence was Aphelocoma ultramarina (0.002) and with the highest frequency Empidonax sp. (0.13), unlike to that found in the disturbed pine forest where the lowest IAR corresponded to Colaptes auratus (0.003) and with the highest appearance was Ptiliogonys cinereus (0.23). The Generalized Linear Model suggested that forest condition and phenology are significantly related to the frequency of species. Limitations on study/implications: In this study it was found that the abundance of birds was affected by the condition of the forest and that the phenology (migration-non-migration), seasonal (rain-dry season), sex and condition of the forest were related to the abundance of birds. Four species classified as under Special Protection and two Threatened according to NOM-059 were registered as well as the presence of four endemic species which highlights the importance of conserving these ecosystems. Findings/conclusions: The fauna communities present in Monte Tláloc highlight the importance of conserving the pine-oak forests since this site is part of the Eje Neovolcanico Transversal.